Midwives - Bohjalian, Chris, 1962- (Oprah's book club., 1998)
In the pastoral community of Reddington, Vermont, during the harsh winter of 1981, Sibyl Danforth makes a life-or-death decision based on fifteen years of experience as a respected midwife -- a decision intended to save a child, a decision that will change her life forever.